Vibrational predissociation of D2HF and H2HF with a new potential energy surface - Krause, P; Clary, D (1998)
The vibrational predissociation of D2HF and H2HF is calculated using a time-dependent method. The calculations use an improved potential energy surface obtained from a fit of new ab initio points to a spherical harmonic expansion. The vibrational predissociation lifetimes and rotational product distributions for D2HF agree well with experiment. For H2HF the vibrational predissociation lifetimes are longer than expected from experiment.